The development of national identity through time in postcolonial Australia in James Tucker’s Ralph Rashleigh, Eleanor dark’s the timeless land, and Kate Grenville’s the secret river - Koo, Xavier Zhi Wei (2015)
While postcolonialism traditionally examines the relationship between the coloniser and the colonised, it often overlooks the role of settlers in postcolonial discourse. In “settled” countries like India, for example, the postcolonial discourse is clear; the British are the colonisers and the Indians are the colonised. The latter thus attempts to undermine the former and dismantle vestiges of (often intangible) colonial structures. However applying the postcolonial discourse to “settler” countries like Australia exposes fundamental problems in the discourse as settlers occupy “an ambivalent position between oppressor and oppressed, plus a complicity with colonialism’s territorial appropriations in the process of forging a resistance to its foreign rule” (Childs, and Williams, 84).